Multilingual RECIST classification of radiology reports using supervised learning - Mottin, Luc; Goldman, Jean-Philippe; Jäggli, Christoph; Achermann, Rita; Gobeill, Julien; Knafou, Julien; Ehrsam, Julien; Wicky, Alexandre; Gérard, Camille L.; Schwenk, Tanja; Charrier, Mélinda; Tsantoulis, Petros; et al. (Frontiers in Digital Health, 2023)
Objectives: The objective of this study is the exploration of Artificial Intelligence and Natural Language Processing techniques to support the automatic assignment of the four Response Evaluation Criteria in Solid Tumors (RECIST) scales based on radiology reports. We also aim at evaluating how languages and institutional specificities of Swiss teaching hospitals are likely to affect the quality of the classification in French and German languages. Methods: In our approach, 7 machine learning methods were evaluated to establish a strong baseline. Then, robust models were built, fine-tuned according to the language (French and German), and compared with the expert annotation. Results: The best strategies yield average F1-scores of 90% and 86% respectively for the 2-classes (Progressive/Non-progressive) and the 4-classes (Progressive Disease, Stable Disease, Partial Response, Complete Response) RECIST classification tasks. Conclusions: These results are competitive with the manual labeling as measured by Matthew’s correlation coefficient and Cohen’s Kappa (79% and 76%). On this basis, we confirm the capacity of specific models to generalize on new unseen data and we assess the impact of using pre-trained language models on the accuracy of the classifiers.